Adverse possession in Kenya: is the doctrine in need of legal reform? - Karimi, J. N. (Strathmore University, 2025)
Adverse possession is a legal doctrine that allows individuals to acquire land ownership after twelve years of continuous and uninterrupted possession, even without the consent of the registered titleholder. While this principle ensures land is utilized efficiently, it has raised concerns about its constitutionality, particularly in modern land registration systems that emphasize the absoluteness of title. This raises concerns about whether adverse possession weakens property rights, legal certainty, and economic stability, especially in jurisdictions like Kenya, where the framework lacks key protections. Using the doctrinal legal research methodology, this study examines the significance of secure land titles in safeguarding property rights and its broader impact on legal stability, economic development, and social order. It also evaluates how Kenya’s adverse possession regime affects private property rights and compares it to the structured approach adopted in the United Kingdom. Unlike Kenya, where adverse possession can occur without the owner’s knowledge, the UK has introduced safeguards such as mandatory notification, land inspections, an extended objection period, public awareness initiatives, and digital integration in land registration. These measures ensure that adverse possession claims do not result in sudden and unfair dispossession. By analyzing contemporary best practices in the UK, this study highlights the need for legal reforms in Kenya to enhance transparency and fairness in adverse possession cases. Implementing notification systems, verification processes, and public education initiatives would help protect property owners while maintaining the principle that land should not remain idle indefinitely. Strengthening Kenya’s legal framework in this area would create a more balanced system that upholds both land security and responsible land use.
Full - text undergraduate research project